Defining ecological thresholds to detect potential ecological risks of offshore wind power using macrobenthic biodiversity and indicator species in Cangnan, China - Wanhong Han; Chen Song; Yurong Zhang; Weiwei Zhou; Yushu Yang; Danyi Ke; Aoxiang Huang; Xiaobo Wang; Qingxi Han (Ecological Indicators)
The construction and operation of offshore wind farms can introduce ecological disturbances that significantly alter benthic habitats, potentially impacting marine biodiversity and ecosystem function. Therefore, investigating the responses of macrobenthic diversity to the development and operation of wind farms and establishing ecological thresholds is crucial for safeguarding benthic ecological quality and promoting the sustainable development of offshore wind energy. To integrate the concept of ecological thresholds with empirical assessments to identify critical environmental limits for sustainable management, macrobenthic samples and water environmental factors were collected from 2021 to 2023 in the Cangnan offshore wind power area and an adjacent control area. Community responses were analyzed via the Shannon–Wiener diversity index, taxonomic β diversity, and conditional probability analysis (CPA) to evaluate the probability of biodiversity damage on the basis of chlorophyll-a (Chl-a) and suspended solids concentrations. Additionally, the pruned exact linear time (PELT) algorithm was applied to detect key CPA change points, and threshold indicator taxa analysis (TITAN) was used to confirm reliable ecological thresholds. The results revealed that species turnover dominated the β diversity in both areas, with higher local species richness in the wind power area. Overall, both areas demonstrated good ecological quality. The CPA revealed that elevated Chl-a concentrations increased the probability of biodiversity damage in both areas, with stronger effects observed in the control area. In the wind power area, moderate increases in the suspended solids concentration appeared to reduce the probability of biodiversity damage, likely due to intermediate disturbance effects, whereas in the control area, the probability of damage increased with increasing suspended solids concentration. Owing to anthropogenic disturbances, no reliable thresholds have been identified in the wind power area. In the control area, the Chl-a damage thresholds were determined to be 1.65 µg/L and 6.79 µg/L, and the suspended solids threshold was 16 mg/L. This study provides insights into the effects of changes in environmental factors on macrobenthic diversity in the Cangnan offshore area due to wind farm construction and operation and identifies robust ecological thresholds. These findings provide a solid scientific basis for the ecological management of benthic quality in offshore wind energy development.